Siddhartha : an Indian tale - Hesse, Hermann, 1877-1962 (Penguin twentieth-century classics, 1999)
Set in India, Siddhartha is the story of a young Brahmin's search for ultimate reality after meeting with the Buddha. His quest takes him from a life of decadence to asceticism, through the illusory joys of sensual love with a beautiful courtesan, and of wealth and fame, to the painful struggles with his son and the ultimate wisdom of renunciation.